POLEMIK CADAR DI TENGAH MASYARAKAT: TINJAUAN PENDAPAT ULAMA DI DALAM KITAB AL-NIQAB ‘ADAH WA LAISA ‘IBADAH KARYA MAHMUD HAMDI ZAQZUQ - Riska Nurulfaizah Utami; Hamid Hodir (Journal Khafi : Journal Of Islamic Studies, 2025)
This study discusses several polemics surrounding the veil (niqab) that have recently emerged in society, namely the stigma of terrorism directed at veiled women, the perception that they are left behind in competition, the definition of syar’i clothing, and the niqab as a symbol of religiosity. In this regard, the author employs a phenomenological approach to understand the phenomenon occurring in society and analyzes the views of scholars found in the book al-Niqab ‘Adah wa Laisa ‘Ibadah, which serves as the primary data of this research, as a response to the phenomenon.The findings of this study are: first, veiled women should refrain from wearing the niqab in societies where it is not part of the local custom, particularly in communities traumatized by acts of terrorism; second, wearing the niqab can obscure a woman’s identity (syakhshiyyah al-mar’ah) in public spaces, causing them to fall behind in competition; third, the definition of syar’i clothing does not require the niqab to cover the face, since the face is not considered aurat, and the niqab has no relation to a woman’s religiosity (tadayyun al-mar’ah) because it is merely a cultural practice rather than a form of worship.